Application of a Lagrangian particle model to the source apportionment for primary macropollutants in Taranto area (South Italy). (1st December 2014) - Giua, Roberto; Morabito, Angela; Tanzarella, Annalisa; Spagnolo, Stefano; Pastore, Tiziano; Bevere, Monica; Valentini, Ettore; La Ghezza, Vito; De Gennaro, Gianluigi; Brusasca, Giuseppe; Tinarelli, Gianni; Assennato, Giorgio
A modelling system has been applied to estimate the annual contribution to the total concentrations of different pollutant sources in Taranto, one of the most industrialized areas in Italy. Industrial sources, traffic, domestic heating and harbour emissions have been taken into account. Modelling system includes 3-dimensional meteorological models SWIFT-SURFPRO with the Lagrangian particle dispersion model SPRAY. The air emissions inventory was partially established using measured data, local activity indicators and emission factors. The meteorology was reconstructed by the SWIFT model from the products supplied, for the year 2007, by the national MINNI project. The annual simulation led to the identification of the main emitting sources for primary pollutants such as NOx, SO2, PM10, PM2.5 and C6 H6 at receptor sites. In addition, a more refined source apportionment was achieved for industrial primary PM10, providing a useful preliminary identification of the main industrial sources emitting dangerous micropollutants, such as POPs and heavy metals.